Diabetes mellitus self-management education at Jimma University Medical Center: evidence-based implementation project. Issue 4 (18th December 2022) - Berhanu, Hiwot; Feyissa, Garumma Tolu; Geleta, Daniel; Sudhakar, Morankar
ABSTRACT: Background: Low and middle-income countries are currently enduring the heaviest global burden of diabetes and diabetes-related mortalities. Diabetes self-management education (DSME) improves patient clinical outcomes, health status, and quality of life. Lack of awareness about best practice guidelines and recommendations may be associated with increased risk of diabetes morbidity and mortality. Objectives: The objective of this study was to improve knowledge and skill of healthcare providers and patients with diabetes by enhancing evidence-based practice through self-management education to increase compliance with best practice recommendations. Methods: JBI's three-phase Practical Application of Clinical Evidence System and Getting Research into Practice audit criteria of diabetes of audit management criteria were used. To understand barriers, 12 audit criteria, patient's medical record handling and educational plan according to set standards were evaluated. To mitigate the barriers, strategies of training and supportive supervision on evidence-based DSME were implemented from 20 April 2018 to 7 June 2018. Sixteen health professionals and 80 patients with diabetes participated in the study conducted in Jimma University Medical Center. Both a baseline and follow-up audit was conducted using the JBI feedback tool. Result: The baseline audit results indicate that 3 of the 12 audit criteria recorded zero percent compliance, whereas other compliances were below 40%, representing poor compliance with the current evidence. The post implementation audit reported 100% compliance for criteria on availability of structured education plan, existence of appropriate training for staff, the presence of education regarding nutrition and medications, while for the remaining criteria on competency of staff members for delivering DSME, assessment of prior diabetes knowledge, status of documentation after each session, and the presence of appropriate referrals or booking the compliance rate was improved to 88%. Similarly, criteria on the presence of individualized education plan improved (0–75%), encountering knowledge regarding physical activity (6–75%), self-monitoring of blood glucose (4–60%), and prevention diabetes complications (10–90%). Conclusion: There were remarkable changes in both patients and care providers on comparison of pre-intervention and post-intervention, particularly in availability of materials, involvement of staff in self-management education, nutrition, and medication.